The investigation of fire growth pattern from different combustible materials - Ainur Nadhirah, Hamsan (2015)
Fire is either man-made or natural. Sometimes it is started on purpose and other times it is an accident. Fire has a purpose, but comes with risks. This study was purposely conducted to identify the differences of fire growth pattern from different combustible materials, present and evaluate the temperature data obtained from the early fire growth stage to the decay stage of each combustible materials and also to identify which type of materials is the highly combustable materials. Each type of materials have its own fire growth pattern. The materials used for this research are the solid state of matter which consists of plastics, papers, woods and the combination of all the solid materials. The method have been used for the study is using fire simulation in the Fire Detection and Supression Simulator (Comprehensive Instrumented Type), Model FDSS-CI which is made of high quality 3 inter-connected chamber and integrated with Thermocouple, Smoke Detector and Control Room. The data was analyse using the Central Fire Detection and Execution System Software (C-FIDES). The finding of this study shows that the mixture of solid that consist of paper, wood and plastic is the most highly combustible materials followed by paper, wood and lastly plastic materials. Besides that, solid mixture combustion shows the highest reading during the fully developed stage which is 138°C followed by paper, wood and plastic. The most short time taken for each combustible materials to achieve rapid growth stage is solid mixture within first 2 minute and followed by paper, wood and plastic. Solid mixture that consist of paper, wood and plastic more easy to ignite followed by paper, wood and plastic. The most rapidly undergo decay stage is paper which is start to decay in the tenth minute followed by solid mixture, wood and plastic. There are several recommendations that can be suggest for the future study. The future study may compare the combustion of wood with coating and wood without coating. Other than that, used materials with different state of matter such as liquid and gaseous and lastly, researcher do combustion in the real home to get the real situation and prediction for fire occurence.